Facile synthesis of three-dimensional flower-like MoO2–graphene nanostructures with enhanced electrochemical performance. Issue 27 (24th June 2016) - Ma, Ying; Jia, Yulong; Wang, Lina; Yang, Min; Bi, Yingpu; Qi, Yanxing
Abstract : Three-dimensional MoO2 –G flower-like nanostructures were synthesized through a facile hydrothermal reaction and showed significantly improved specific capacitance, good rate capability and cycling stability. Abstract : Novel three dimensional MoO2 –graphene (MoO2 –G) flower-like nanostructures are synthesized via a facile hydrothermal reaction. It has been shown that the MoO2 –G demonstrates enhanced supercapacitive performance compared to pure MoO2 particles. The excellent electrochemical performance is attributed to the introduction of graphene and a hierarchical nanostructure, providing a large surface area and low equivalent series resistance.